Studies of two aspects of business in Europe - Cranfield Management Development Programme no. 3. (College of Aeronautics, 1965)
The Cranfield Management Development Programme is an intensive ten week course for middle management aged 28 - 38. The courses which are held twice yearly started in 1964; the third of these MDP III was held from October - December, 1965. The members of the course are drawn from a variety of businesses and have previous experience in one or more of the main fields of business activity, e.g. general management, marketing, production. As part of the course two weeks are devoted to studying business conditions in Europe. For this tour the members are formed into small groups who study particular projects. MDP III were in Europe from 14th - 27th November, 1965 during which period the following cities were visited; Lyon, Zurich, Hanover, Rotterdam and Brussels. In each city discussions were arranged with a representative cross-section of the business community. These included British Embassy Staff, British Chambers of Commerce, local bankers, industrial companies, advertising agents, Trade Union officials, management consultants and British subsidiaries. On their return from Europe a meeting was held at the Royal Overseas League in London where the members of the course presented their findings to a group of businessmen, and representatives of the Export Council for Europe and the Confederation of British Industries. This report is split into two parts representing the work of the two project groups.